Factors Influencing Social Entrepreneurial Intention Among Students at Higher Learning Institutions in Melaka - Muhammad Arif, Hasan (2022)
Social entrepreneurship has gained popularity in developing countries and contributed to the economy by addressing the countries' social and environmental problems. However, there is a significant lack of study on social enterprises especially in Malaysia (specifically in Melaka) which may result in subsequent social and environmental problems. Therefore, there is an urgency to increase the number of social entrepreneurs to solve the issues. The appropriate and effective factors that can influence the intention to become social entrepreneurs need to be researched and promoted to encourage students in higher learning institutions in Melaka to be social entrepreneurs. The Theory of Planned Behaviour is used to examine the relationships between attitude toward becoming a social entrepreneur, social worth, moral obligation, self-efficacy, perceived social support, and social entrepreneurial intention among students at higher learning institutions (HEI) in Melaka. Awareness was selected as a moderator. The study used a convenient sampling method and 765 students responded. Partial Least Square Structural Equation Modelling (PLSSEM) version 3.3.2 was used to test the relationship and effect among the variables. All of the factors are significantly related to social entrepreneurship intention. Students can be developed as future social entrepreneurs by cultivating their attitude towards becoming social entrepreneurs, moral obligation to helping the needy, a sense of social worth when helping others, self-efficacy in becoming social entrepreneurs, and increasing their knowledge of available support. Awareness moderates the relationship between social worth and social entrepreneurial intention. Social worth is considered a new determinant and awareness a new moderator in the social entrepreneurship study. It is recommended that ministries and HEI to create more awareness and concentrate on building attitude, moral obligations and self-efficacy among students.